Population fluctuation and parasitism of Aleurothrixus floccosus (Hemiptera: Aleyrodidae)in citrus trees from Atacama Desert, Chile - Tello-Mercado, Víctor; Zarzar-Maza, Miguel (Revista Colombiana de Entomología, 2021)
The effect of three different types of crop management on parasitism of Aleurothrixus floccosus in the Atacama Desert was studied. The studied parasitoids were: Cales noacki, Eretmocerus paulistus, Amitus spiniferus, and the hyperparasitoid Signiphora sp. The study was performed in Pica Oasis, located in the Atacama Desert, Tarapacá region, Chile, from February 2009 until February 2011. Three orchards were selected based on the type of plantation: the Bajo Miraflores Sector with plantation frames (5 x 5 m) and pruning management; the San Lorenzo Sector without plantation frames or pruning management; and Miraflores Sector that represents a mixed system between both of them. Two sampling procedures were applied. One was of the absolute type, in which 36 leaves per tree were collected from four labeled trees that were sampled twice a month, and the other was collected through yellow sticky chrome-attracting traps set in the central part of each of the labeled trees used for absolute sampling. The results indicate that in the Oasis of Pica, the different stages of A. floccosus are distributed throughout the year; with all stages represented during every month. The three sampled sectors exhibited different population levels of A. floccosus. The hyperparasitoid Signophora sp. presented the highest population density. The average parasitism percentage of A. floccosus in Pica was lower than 15 %.